A developmental cascade model of behavioral sleep problems, emotional and attentional self-regulation across early childhood - Berthelsen, Donna; Nicholson, J; Walker, S; Williams, Kate; Nicholson, Jan M; Walker, Sue; Williams, Kate E (My University, 2015)
This paper documents the longitudinal and reciprocal relations among behavioral sleep problems, emotional and attentional self-regulation in a population sample of 4109 children participating in the Growing Up in Australia: The Longitudinal Study of Australian Children (LSAC) – Infant Cohort. Maternal reports of children’s sleep problems and self-regulation were collected at five time points from infancy to 8-9 years of age. Longitudinal structural equation modeling supported a developmental cascade model in which sleep problems have a persistent negative effect on emotional regulation, which in turn contributes to ongoing sleep problems and poorer attentional regulation in children over time. Findings suggest that sleep behaviors are a key target for interventions that aim to improve children’s self-regulatory capacities.
Keywords: Children -- Early childhood; Child Development -- Sleep; Childhood and child development; Child Development; Children; Sleep; Early childhood; Childhood and child development